1988
DOI: 10.1073/pnas.85.14.5291
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and cloning of fasciclin I and fasciclin II glycoproteins in the grasshopper.

Abstract: Monoclonal antibodies were previously used to identify two glycoproteins, called fasciclin I and II (70 and 95 kDa, respectively), which are expressed on different subsets of axon fascicles in the grasshopper (Schistocerca americana) embryo. Here the monoclonal antibodies were used to purify these two membrane-associated glycoproteins for further characterization. Fasciclin II appears to be an integral membrane protein, whereas fasciclin I is an extrinsic membrane protein.The amino acid sequences of the amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 29 publications
0
36
0
1
Order By: Relevance
“…540,000 phage from a ~gtl 1 cDNA library constructed from S. americana staged at 40% of development (Snow et al 1988) were screened at low stringency (hybridization conditions--30% formamide, 5 × SSC [SSC: 0.15 M NaC1, 0.15 M sodium citrate], 1% SDS, 1% BLOTTO [BLOTTO: 10% Carnation nonfat dry milk] at 42°C; wash conditions--2 × SSC, 0.1% SDS at 50°C). An 850-bp subclone (850PN) from D. melanogaster dpp con-…”
Section: Methodsmentioning
confidence: 99%
“…540,000 phage from a ~gtl 1 cDNA library constructed from S. americana staged at 40% of development (Snow et al 1988) were screened at low stringency (hybridization conditions--30% formamide, 5 × SSC [SSC: 0.15 M NaC1, 0.15 M sodium citrate], 1% SDS, 1% BLOTTO [BLOTTO: 10% Carnation nonfat dry milk] at 42°C; wash conditions--2 × SSC, 0.1% SDS at 50°C). An 850-bp subclone (850PN) from D. melanogaster dpp con-…”
Section: Methodsmentioning
confidence: 99%
“…The antibody was used to screen a 9-12-hour embryonic Drosophila phage-gt11 cDNA library (Snow et al,1988) that identified two phages containing a 435-bp EcoR1 fragment that did not include the full open reading frame. A radiolabeled probe derived from this fragment was used to screen the cDNA library and identify a large open reading frame (Hortsch et al, 1990).…”
Section: M19mentioning
confidence: 99%
“…Fasciclin I and Fasciclin I1 are membrane-associated glycoproteins that are expressed in an ordered, temporally and spatially dynamic pattern on different neurons in the developing central and peripheral nervous system of the grasshopper and other insects. (Bastiani et al, 1987;Harrelson and Goodman, 1988;Snow, Zinn, Harrelson, et al, 1988;Zinn, McAllister, and Goodman, 1988). The Fasciclins are thought to be specific cell-cell recognition molecules with adhesive-binding properties.…”
Section: Developmental and Evolutionarymentioning
confidence: 99%